(untitled) (Research, Society and Development, 2022)
Objective: To measure the perception of patient safety culture in the home care service in Maceió. Method: Cross-sectional study, developed with 88 professionals, who answered a sociodemographic questionnaire and the Safety Attitudes Questionnaire - Short form 2006, validated for Portuguese. Data collection took place between November 2018 and January 2019. Descriptive and inferential statistics were used, considering a significant p-value equal to or less than 0.05. The cutoff point for a positive assessment was ≥75 points. Results: The means of the domains ranged from 69.83 for the perception of the Management-Secretary of Health to 87.55 for Job Satisfaction. Professionals with up to 10 years of experience are more satisfied with their work. Conclusion: The patient safety culture is not strengthened in this service, given the low scores in the domains of stress perception, health department management and working conditions.